A new lure for Thrips major - Teulon, D.A.J.; Nielsen, M-C.; Kogel, W.J. De; Van_Tol, R.W.H.M.; Davidson, M.M. (New Zealand Plant Protection, 2008)
The addition of either a prototype lure or a commercially available lure LUREMTR increased capture of the pest Thrips major Uzel on sticky traps in a commercial greenhouse and an outdoor crop in the Netherlands This pest species is widespread throughout Europe but has not yet been confirmed present in New Zealand In greenhouses of capsicum sticky traps with a prototype lure caught between 12 to 60 times more T major compared to traps without the prototype lure In an outdoor crop of leek traps with the commercial lure LUREMTR caught between 2 to 13 times more T major than traps without the lure Thrips major breeds on a range of flowering plants and has been implicated in fruit loss in nectarine peach and strawberries Thrips major can cause extensive damage through feeding and ovipositioning although it has not been found to vector tospoviruses